The Well-Being of Siblings of Individuals with Autism. (30th April 2013) - Green, Laura
Abstract : Objective . The purpose of this review of the literature was to summarise studies regarding the psychosocial impact of growing up with a sibling with autism and to identify gaps in the related literature. Methods . Electronic databases were reviewed in order to critically appraise the 14 articles relevant to the topic. The search included a combination of the following key words: autism*, quality of life, well-being, sibling*, ASD, ASD sibling*, family, adjust*, psychological functioning. Results . The majority of studies involved mixed children and adolescent samples, leading to confounding results and an inability to draw accurate conclusions about these distinct life stages. Autism appears to contribute to unique environmental stressors for the typically developing sibling. When experienced in the context of additional demographic risk factors, these stressors can result in difficulties adjusting to the demands of a special-needs child. Despite some vulnerability to behavioural and emotional dysfunction in at-risk children, siblings have the potential to not only adjust but to thrive in the face of disability adversity. Conclusion . Growing up with a sibling with autism appears to manifest in both positive and negative outcomes for siblings, depending upon important demographical, family, and individual variables.